Frontispiece: Towards Upcycling Biomass‐Derived Crosslinked Polymers with Light. Issue 31 (25th July 2022) - Singathi, Ravichandranath; Raghunathan, Ramya; Krishnan, Retheesh; Kumar Rajendran, Saravana; Baburaj, Sruthy; Sibi, Mukund P.; Webster, Dean C.; Sivaguru, Jayaraman
Abstract : Renewable Polymers . In their Communication (e202203353 ), Mukund P. Sibi, Dean C. Webster, Jayaraman Sivaguru et al. highlight a methodology for the generation of photodegradable and recyclable cross‐linked polymers from biomass.